1974
DOI: 10.1073/pnas.71.10.4032
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Antibodies with Shared Idiotypy: The Complete Sequence of the Heavy Chain Variable Regions of Two Immunoglobulin M Anti-Gamma Globulins

Abstract: The complete amino acid sequence of the heavy chain variable regions of two different molecules of immunoglobulin M anti-gamma globulin has been determined. These proteins, from different human patients, had independently been shown to share idiotypic specificity. Only eight sequence differences were discernible for the entire length of their heavy chain variable regions. Five of the differences occurred outside hypervariable regions, while three were placeable within such regions. A comparison of these molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(45 citation statements)
references
References 40 publications
3
42
0
Order By: Relevance
“…B-CLL is not associated with HCV infection (25), but the antigeninduced expansion of clonotypic B cells may be similar. Over twenty-five years ago, our laboratory showed that the similarity among heavy chain complementaritydetermining regions (CDRs) 2 and 3 in the mixed cryoglobulin rheumatoid factors Pom and Lay (26,27) was perhaps an early hint of similar results to those reported by Ghiotto et al in this issue (16). EMC now is thought to arise from CD5 -immunocytomas that are considered marginal zone lymphomas.…”
Section: Clonotypic Igs Are Seen In Other Disease Processessupporting
confidence: 68%
“…B-CLL is not associated with HCV infection (25), but the antigeninduced expansion of clonotypic B cells may be similar. Over twenty-five years ago, our laboratory showed that the similarity among heavy chain complementaritydetermining regions (CDRs) 2 and 3 in the mixed cryoglobulin rheumatoid factors Pom and Lay (26,27) was perhaps an early hint of similar results to those reported by Ghiotto et al in this issue (16). EMC now is thought to arise from CD5 -immunocytomas that are considered marginal zone lymphomas.…”
Section: Clonotypic Igs Are Seen In Other Disease Processessupporting
confidence: 68%
“…The structural basis of human autoantibodies has been the subject of intensive investigation for more than four decades (41,61). Initial studies of rheumatoid factor paraproteins provided critical insights into the structural basis of idiotypes and Ab diversity while also hinting at a role for somatic hypermutation first recognized by seminal studies of mouse L chains (62).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of methionine residues at positions 34 and 83 of the heavy chain variable region in all mouse phosphorylcholine-binding proteins has facilitated their sequence determination by the procedures employed for M603 (17). These proteins provide a unique opportunity to evaluate primary structural differences among a group of antibodies demonstrating activity for the same chemically defined hapten.…”
Section: Discussionmentioning
confidence: 99%